Sensory evaluation of cashew (Anacardium occidentale L.) and pineapple (Ananas comosus L.) Juice with lemongrass (Cymbopogon citratus) - Arman H. Sumandal (The Bioscan, 2026)
This experimental study aimed to analyze the sensory characteristics of cashew-pineapple juice enriched with lemongrass in different proportions in terms of appearance (color) and (degree of clarity), aroma, taste (sweetness), (sourness) and (aftertaste), flavor, and texture. The analyses revolved around the 30 expert evaluators who examined the sensory characteristics of the products. Both descriptive and inferential measures were employed to answer the queries raised in this study. This study revealed that the proportion with high pineapple content (25 grams cashew apple & 75 grams pineapple juice) has a deeper yellow color and is cloudier with visible pulp. This proportion also resulted in a fruity and citrusy aroma with a harmonious blend of natural sweetness but has minimal sourness and a citrusy aftertaste. Furthermore, the findings of this study showed that lemongrass can be used as an enrichment in cashew- pineapple juice in the form of an extract. This added natural component not only improves the nutritious qualities of the juice but also its sensory attributes due to its distinct aroma and pleasant aftertaste. Moreover, a wide dissemination of the results of this study is encouraged through training, seminars, and workshops. Also, since Cashew is regarded as the “One Town, One Product” of Palawan, the province's tourism industry may consider this product as an additional local product that can be commercialized not only by local tourists but also to foreign tourists. This may also provide local cashew farmers with additional income since not only the cashew nuts will be commercialized but also the cashew apples.